Clinicohematological profile of patients of sepsis admitted in intensive care unit in a tertiary care hospital in Western India - Patel, Vipul; Shah, Amit; Muley, Arti (International Journal of Research in Medical Sciences, 2020)
Background: Sepsis is a life-threatening medical condition triggered due to body’s response to an infection. If empirical treatment for sepsis and bacteraemia is held up it will increase chances of mortality as well as duration of stay and cost. Hence, there is a need for risk stratification. So, we planned to study the clinicohematological profile of patients of sepsis admitted to this hospital in ICU. Methods: This was an observational study. A total of 50 patients of sepsis were included. All included participants were subject to CBC, RFT, LFT, RBS, Urine RM, ESR, chest X-ray, USG Abdomen. Laboratory evaluations were performed in the institutional pathology and biochemistry labs. Data was analysed to assess the clinicohematological profile of the patients of sepsis to identify common factors which if taken care of in time can reduce development to sepsis and the morbidity and mortality related to it. Results: Most common presenting complaint was fever (72%), followed by altered sensorium (58%), vomiting (30%), jaundice (30%) and breathlessness (20%). Most noticed signs were pallor (36%), icterus (36%), edema (6%), reduced air entry (34%) and crepitations (26%). Most common source of the infection were abdomen (28%), urinary tract infection (26%) and community acquired pneumonia (24%). Conclusions: Most common presenting complaints were fever, breathlessness, altered sensorium. Most common source of sepsis were urinary tract infection, lung, and abdomen which if adequately treated in time would aid in reducing the number of sepsis patients and thus will control the morbidity, mortality and cost associated with sepsis.